Open Eric-Luu opened 1 year ago
If I have 3 binary bits a, b, and c, then the equation:
h = abc + (1-a) (1-b) (1-c)
should evaluate to:
h = ab + ac + bc - a - b - c + 1
However, the resulting compiled structure of h = abc + (1-a) (1-b) (1-c) still keeps an a*b term.
If I have 3 binary bits a, b, and c, then the equation:
h = abc + (1-a) (1-b) (1-c)
should evaluate to:
h = ab + ac + bc - a - b - c + 1
However, the resulting compiled structure of h = abc + (1-a) (1-b) (1-c) still keeps an a*b term.